The Effect Of System Quality, Information Quality, and Network Quality on The Quality of Electronic Local Tax Information System Services (Si Pakde) In Restaurant Tax Payments at The Regional Revenue Agency of Jombang Regency - Angrraeni, Natasya Dinda; Pradana, Galih Wahyu; Eprilianto, Deby Febriyan; Fitrie, Ravienda Anita (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The implementation of the Electronic Regional Tax Information System (SI PAKDE) by the Jombang Regency Regional Revenue Agency (Bapenda) aims to improve the quality of regional tax services. However, there are indications that taxpayers still face technical obstacles in the form of unstable network connections, system delays, and inadequate information clarity. This study examines the influence of three dimensions of quality, application system quality, information content quality, and network infrastructure quality on the perception of SI PAKDE service quality. The research method uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique assisted by SmartPLS 4 software. The research sample consisted of 98 restaurant taxpayers who actively use SI PAKDE, selected through proportionate stratified random sampling. The results showed that simultaneously the three independent variables significantly influenced service quality with an R-square value of 0.865, which means these variables were able to explain 86.5% of the variation in service quality. Partially, it was found that network quality had a positive and most dominant influence on service quality (path coefficient 0.607; p = 0.000). System quality also had a significant effect, but with a lower magnitude (path coefficient 0.242; p=0.046). Conversely, information quality was found to have no significant effect on service quality in the context of restaurant taxpayers' use of the PAKDE Information System (path coefficient 0.114; p=0.354).